Cobalt‐Catalyzed Negishi Cross‐Coupling Reactions of (Hetero)Arylzinc Reagents with Primary and Secondary Alkyl Bromides and Iodides1. Issue 15 (18th February 2015) - Hammann, Jeffrey M.; Haas, Diana; Knochel, Paul
Abstract We report a cobalt‐catalyzed cross‐coupling of di(hetero)arylzinc reagents with primary and secondary alkyl iodides or bromides using THF‐soluble CoCl2⋅2 LiCl and TMEDA as a ligand, which leads to the corresponding alkylated products in up to 88 % yield. A range of functional groups (e.g. COOR, CN, CF3, F) are tolerated in these substitution reactions. Remarkably, we do not observe rearrangement of secondary alkyl iodides to unbranched products. Additionally, the use of cyclic TBS‐protected iodohydrins leads to trans‐2‐arylcyclohexanol derivatives in excellent diastereoselectivities (up to d.r.=99:1).